The Effect of Budget Planning, Budget Implementation, and Direct Expenditure on Budget Realization Mediated by Organizational Commitment - putri, Gita Varina; Fitriasuri; Helmi, Sulaiman; Fransisca, Septiani (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of budget planning, budget implementation, and direct expenditure on budget realization, with organizational commitment as a mediating variable at the Social Service Office of Palembang City. Using a quantitative survey of 95 respondents selected through a census technique, data were analyzed with SEM-PLS. The findings show that budget planning and implementation positively and significantly influence budget realization, while direct expenditure has a negative effect. Organizational commitment mediates the relationship between planning, implementation, and realization. These results highlight that successful budget realization depends not only on technical processes but also on organizational commitment as a critical behavioral factor. Keywords: Budget Planning; Budget Implementation; Direct Expenditure; Organizational Commitment; Budget Realization